2021
DOI: 10.3390/pr9050784
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities, Metabolites, Fermentation Quality and Aerobic Stability of Whole-Plant Corn Silage Collected from Family Farms in Desert Steppe of North China

Abstract: Whole-plant corn silages on family farms were sampled in Erdos (S1), Baotou (S2), Ulanqab (S3), and Hohhot (S4) in North China, after 300 d of ensiling. The microbial communities, metabolites, and aerobic stability were assessed. Lactobacillusbuchneri, Acinetobacter johnsonii, and unclassified Novosphingobium were present at greater abundances than others in S2 with greater bacterial diversity and metabolites. Lactobacillus buchneri, Lactobacillus parafarraginis, Lactobacillus kefiri, and unclassified Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(70 reference statements)
1
16
0
1
Order By: Relevance
“…Results were consistent with those of previous studies [9,11,12,14,27]. Moreover, Xu et al [26], Drouin et al [28] and Wang et al [29] revealed that Lactobacillus was the dominant bacterial genus in the final whole-plant corn silage. This showed that Lactobacillus usually dominates bacterial community succession in whole-plant corn silage during fermentation.…”
Section: Discussionsupporting
confidence: 91%
“…Results were consistent with those of previous studies [9,11,12,14,27]. Moreover, Xu et al [26], Drouin et al [28] and Wang et al [29] revealed that Lactobacillus was the dominant bacterial genus in the final whole-plant corn silage. This showed that Lactobacillus usually dominates bacterial community succession in whole-plant corn silage during fermentation.…”
Section: Discussionsupporting
confidence: 91%
“…The whole-plant corn silage is a microbial fermentation product, analyzing the bacterial and fungal communities is helping to understand the different fermentation quality and aerobic stability among silages (Wang et al, 2021). The key microorganisms are Lactobacillus group during fermentation process in whole-plant corn silage (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the past 5 years, research in this area has primarily focused on the microbial communities in whole-plant corn silages. As the microbial community composition plays a crucial role in the fermentation quality and aerobic stability of silage, it is necessary to assess the bacterial and fungal communities to explain the different fermentation quality and aerobic stability among silages (Wang et al, 2021). Previous studies revealed the microbial community dynamics in whole-plant corn silages inoculated with lactic acid bacteria (LAB) (Keshri et al, 2018;Xu et al, 2020b) and derived from materials obtained from three areas in Iran (Gharechahi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting evaluation of the differences in microbial communities, metabolites, and the aerobic stability between whole-plant corn silages from different areas of Inner Mongolia in North China has been assessed by Wang et al [15]. Moreover, the same authors investigated the variation of bacterial dynamics during the fermentation process in whole-plant corn silages processed in Heilongjiang, Inner Mongolia and Shanxi of North China [16].…”
mentioning
confidence: 99%